Shortening of Titin’s Elastic Tandem Ig Segment Leads to Diastolic Dysfunction - Chung, Charles S (2013)
BACKGROUND: Diastolic dysfunction is a poorly understood but clinically pervasive syndrome that is characterized by increased diastolic stiffness. Titin is the main determinant of cellular passive stiffness. However, the physiological role that titin’s tandem Ig segment plays in stiffness generation and whether shortening this segment is sufficient to cause diastolic dysfunction needs to be established. METHODS AND RESULTS: We generated a mouse model in which nine immunoglobulin (Ig)-like domains (Ig3-11) were deleted from the proximal tandem Ig segment of titin’s spring region (IG KO). Exon microarray analysis revealed no adaptations in titin splicing, while novel phospho-specific antibodies did not detect changes in titin phosphorylation. Passive myocyte stiffness was increased in the IG KO and immunoelectron microscopy revealed increased extension of the remaining titin spring segments as the sole likely underlying mechanism. Diastolic stiffness was increased at the tissue and organ levels, with no consistent changes in ECM composition or ECM-based passive stiffness, supporting a titin-based mechanism for in-vivo diastolic dysfunction. Additionally, IG KO mice have a reduced exercise tolerance, a phenotype often associated with diastolic dysfunction. CONCLUSIONS: Increased titin-based passive stiffness is sufficient to cause diastolic dysfunction with exercise intolerance.